2016
DOI: 10.5812/hepatmon.34763
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Occult Hepatitis B Infection Among Injecting Drug Users in Tehran, Iran

Abstract: BackgroundHepatitis B virus (HBV) infection is a major health problem worldwide.ObjectivesThe aim of this study was to investigate the frequency of occult hepatitis B infection (OBI) and its associated risk factors, together with the molecular characterization of the virus in injecting drug users of Tehran.Patients and MethodsThe study consisted of 229 injecting drug users. Serum samples were collected and tested for the presence of hepatitis B core antibody (HBcAb) and hepatitis B surface antigen (HBsAg) by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
4
10
0
Order By: Relevance
“…40 Although, in previous studies non-DI subgenotypes, such as D2 and D3, have been rarely reported from Iran. 19 Almost all samples of this project had viral loads lower than 1.3 × 10 3 copies/mL, which is in line with most of previous studies that reported very low and undetectable viral loads 26,27,39 ; OBI usually defined with viral loads lower than 1000 copies/mL. 41 This is mainly related to long-standing persistence of viral cccDNA, presence of replication-competent isolates and intense suppression of viral activity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…40 Although, in previous studies non-DI subgenotypes, such as D2 and D3, have been rarely reported from Iran. 19 Almost all samples of this project had viral loads lower than 1.3 × 10 3 copies/mL, which is in line with most of previous studies that reported very low and undetectable viral loads 26,27,39 ; OBI usually defined with viral loads lower than 1000 copies/mL. 41 This is mainly related to long-standing persistence of viral cccDNA, presence of replication-competent isolates and intense suppression of viral activity.…”
Section: Discussionsupporting
confidence: 84%
“…This could be due to neighboring with Afghanistan; there is a heterogeneous distribution of HBV in Afghanistan . Although, in previous studies non‐DI subgenotypes, such as D2 and D3, have been rarely reported from Iran …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The detection of HBV genotype D is in line with previous epidemiological studies in Iran (29,30) and the neighbouring countries (8,31,32). Although HBV D1 is the major subgenotype circulating in Iran (33), partial S gene sequences in the present study did not provide enough data for HBV subgenotyping (34).…”
Section: Discussionsupporting
confidence: 87%
“…The gold standard for diagnosis of OBI is liver biopsy and detecting the presence of HBV DNA in hepatocytes (1)(2)(3). An alternative method for diagnosis of OBI is detecting HBV DNA in peripheral blood samples.…”
Section: Introductionmentioning
confidence: 99%